Analisis Perbandingan Efektivitas Injeksi Intra Vitreal Anti – Vegf Ranibizumab dan Brolucizumab Untuk Pengobatan Retinopati Diabetik di RS Puri Cinere Tahun 2022 – 2023 dan Tinjauannya dalam Islam - Saskya Putri Prameswari; Mokoginta, Saskia Nassa; Polana, Rita; Haryono, Tri Agus; Fazlurrahman Anshar, Muhammad (Junior Medical Journal, 2025)
This study aims to determine the comparison of the effectiveness of Ranibizumab and Brolucizumab injection for diabetic retinopathy patients and its review in Islamic views. The results of this study showed that there were 20 patients with diabetic retinopathy in Puri Cinere Hospital. Patients with diabetic retinopathy who used Ranibizumab were 8 people (40%) while those who used Brolucizumab were 12 people (60%). Of the total 20 patients who used these two drugs, 13 patients experienced improvement, while 7 others showed no improvement. Patients with diabetic retinopathy mostly used Brolucizumab therapy (56%) compared to Ranibizumab (43%). According to Islam, the description of diabetic retinopathy is a research activity for the development of science in the field of medicine. Patients with diabetic retinopathy should maintain a healthy lifestyle and seek treatment with halal medicine.